2021
DOI: 10.1161/jaha.120.019667
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Transcriptional Landscape of Human End‐Stage Heart Failure

Abstract: Background Transcriptomic studies have contributed to fundamental knowledge of myocardial remodeling in human heart failure (HF). However, the key HF genes reported are often inconsistent between studies, and systematic efforts to integrate evidence from multiple patient cohorts are lacking. Here, we aimed to provide a framework for comprehensive comparison and analysis of publicly available data sets resulting in an unbiased consensus transcriptional signature of human end‐stage HF. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 64 publications
2
46
0
Order By: Relevance
“…Expansion of immune cell populations might arise from recruitment of circulating cells or proliferation of resident cells. In our samples, proliferating myeloid cells decreased, as was previously observed in other DCM studies ( 85 ). Myeloid recruitment through the CCR2/CCL2 axis, which is primarily mediated by vFB3, was decreased in all samples, with particularly dysregulated fibroblast-to-macrophage interactions in TTN .…”
Section: Discussionsupporting
confidence: 90%
“…Expansion of immune cell populations might arise from recruitment of circulating cells or proliferation of resident cells. In our samples, proliferating myeloid cells decreased, as was previously observed in other DCM studies ( 85 ). Myeloid recruitment through the CCR2/CCL2 axis, which is primarily mediated by vFB3, was decreased in all samples, with particularly dysregulated fibroblast-to-macrophage interactions in TTN .…”
Section: Discussionsupporting
confidence: 90%
“…Instead, we propose enrichment analysis to be superior, as it focuses on the direction of regulation and not the effect size of individual genes. ( 23 ) Of note, this approach requires access to raw or processed data. Following the enrichment analysis strategy, a more sophisticated comparison of the chronic CCl 4 mouse model and human studies identified a set of 228 genes with similar regulation in mouse and human CLDs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical evidence revealed that CCDC80 expression was significantly increased in patients with pulmonary arterial hypertension and heart failure. 40 , 41 , 42 This evidence indicates a close association between CCDC80 and cardiovascular system.…”
Section: Resultsmentioning
confidence: 63%